2015
DOI: 10.1189/jlb.3a1214-598r
|View full text |Cite
|
Sign up to set email alerts
|

IFNAR signaling directly modulates T lymphocyte activity, resulting in milder experimental autoimmune encephalomyelitis development

Abstract: Although interferon-β is used as first-line therapy for multiple sclerosis, the cell type-specific activity of type I interferons in multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis, remains obscure. In this study, we have elucidated the in vivo immunomodulatory role of type I interferon signaling in T cells during experimental autoimmune encephalomyelitis by use of a novel transgenic mouse, carrying a cd2-ifnar1 transgene on a interferon-α/β receptor 1 null genetic background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Thus, the overall impact of type I IFN signaling during mycobacterial infection may be a composite of differential effects on myeloid and lymphocyte cell functions. Mouse models that allow assessment of the impact of type I IFN signaling in specific cell subsets such as T cells ( 127 ) might prove valuable in dissecting the direct impact of type I IFNs on T cell functions during M. tuberculosis infection.…”
Section: Consequences Of Type I Ifn Signaling During M Tubmentioning
confidence: 99%
“…Thus, the overall impact of type I IFN signaling during mycobacterial infection may be a composite of differential effects on myeloid and lymphocyte cell functions. Mouse models that allow assessment of the impact of type I IFN signaling in specific cell subsets such as T cells ( 127 ) might prove valuable in dissecting the direct impact of type I IFNs on T cell functions during M. tuberculosis infection.…”
Section: Consequences Of Type I Ifn Signaling During M Tubmentioning
confidence: 99%
“…A study performed during the disease course pointed out that endogenous IFN-β reduces the frequency of CD4 + IL-17 + LN cells isolated on day 4 of EAE, but this effect was not observed on day 10 [58]. A recent study by our group, using ifnar1 Tecxl mice that express IFNAR selectively on T cells, showed that endogenous IFN-β acted directly on T cells in vivo ,reducing Th17responses in the periphery on day 10 of EAE, but this effect was reversed on day 17 [62]. In addition, silencing of irf7, a factor that mediates IFN-β production, in CD4 + T cells from MS patients, led to secretion of higher levels of IL-17A and IL-17F, suggesting that endogenous IFN-β suppressed Th17 responses [63].…”
Section: Th17 Cellsmentioning
confidence: 61%
“…Noteworthy, there are only two studies that reveal this specified action, using two different transgenic mouse models. Prinz et al generated ifnar1 fl/fl CD4 Cre mice that lack IFNAR on T cells [52], while our group reversely generated IFNAR1 Texcl mice that express IFNAR exclusively on T cells [62]. These two different approaches enriched our knowledge on the beneficial effect of IFN-β on T cells and its dependence on the cellular environment and disease stage.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Type I IFN are powerful signals that can modify the functionality of many cell types, including CD4 + T cells, which play a major role in the two diseases. For example, in EAE, IFN-I signaling in T cells can directly impair Th17 differentiation 71 . During blood stage malaria, CD4 + T cell-intrinsic IFN-I signaling induces T-bet and Blimp-1 expression, thereby promoting IL-10 + Tr1 responses in mice 72 as well as in humans 73 .…”
Section: Discussionmentioning
confidence: 99%